2022
DOI: 10.1155/2022/2798019
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] An Analysis of the Cultivation Methods of Visual Communication Design in New Media Environment

Abstract: In order to better adapt to the teaching development needs of visual communication design in the new media environment, a method of visual communication design training based on the ecological environment of the new media environment is proposed. This method constructs a web-based professional course network teaching platform by cultivating practical design talents under the new platform, new environment, and new technology, starting from the perspective of practical application, starting from the teaching pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The type of information on the Internet has also gradually changed from a single text-based approach to a multimedia information-based presentation with graphics, images, animations, videos, and so on. Nowadays, the Internet has become a vast source of multimedia information [5][6][7][8][9][10]. Since the 21st century, digital cameras and digital camcorders have become increasingly popular, and multimedia content has expanded exponentially [11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The type of information on the Internet has also gradually changed from a single text-based approach to a multimedia information-based presentation with graphics, images, animations, videos, and so on. Nowadays, the Internet has become a vast source of multimedia information [5][6][7][8][9][10]. Since the 21st century, digital cameras and digital camcorders have become increasingly popular, and multimedia content has expanded exponentially [11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%